Characterization of Yersinia enterocolitica Biotype 1A Strains Isolated from Swine Slaughterhouses and Markets. (6th February 2013) - Paixão, Renata; Moreno, Luisa Zanolli; Sena de Gobbi, Débora Dirani; Raimundo, Daniele Cristine; Hofer, Ernesto; Matté, Maria Helena; Ferreira, Thais Sebastiana Porfida; Gomes, Vasco Tulio de Moura; Costa, Barbara Leticia Pereira; Moreno, Andrea Micke
Abstract : Yersinia enterocolitica is an important foodborne pathogen that causes illness in humans and animals. Y. enterocolitica is also the most heterogeneous species of the genus and is divided into distinct serotypes and over six biotypes. Y. enterocolitica biotype 1A strains are classically considered as nonpathogenic; however, some biotype 1A isolates have been considered as causative of gastrointestinal disease, yielding symptoms indistinguishable from those produced by pathogenic biotypes. Even after decades of isolation of clinical strains, the pathogenic mechanisms of these isolates are still not fully understood. In the present study, 122 Yersinia enterocolitica biotype 1A strains isolated from swine slaughterhouses and meat markets in Sao Paulo, Brazil, were characterized according to the presence of the virulence genes ail, vir F, and yst A. A total of 94 strains were positive to at least one virulence gene (77.05%), and 67 were positive to all of them (54.92%). Twenty-two strains were submitted to PFGE genotyping resulting in 22 distinct pulsotypes, varying from 50% to 84% of genetic similarity. Any clustering tendency among pulsotypes related to origin, isolation site, or even virulence profile was not observed. The present study reports an important contamination of the environment in swine slaughterhouses, meat markets, and pork, by potentially virulent Y. enterocolitica biotype 1A.